Urban–Rural Influences on Parenting and Theory of Mind Development: An Intracultural Comparative Study in Indonesia - Rizqi, Nisa Praditya Ar; Kuntoro, Ike Anggraika; Halim, Lathifah (UI Scholars Hub, 2022)
Culture has a significant influence on parenting and the Theory of Mind (ToM). The impact of intracultural aspects requires greater investigation. Our research explores the intracultural influence of the location of the domicile of families on young children’s acquisition of ToM and parenting practices. Surveys were given to 350 children (ages 3 to 6) and their parents. Domiciles were divided into three groups: i) the urban area of Jakarta, ii) the suburbs in satellite cities near Jakarta (Bogor and Tangerang), and iii) the rural area of Bukittinggi. This research aims to determine whether there are significant differences in parenting practices and ToM between the three groups. Most participants are of a low socioeconomic level. The comparative results show significant differences in the ToM performance of children living in the three areas; children living in rural areas tend to have higher scores on ToM, followed by urban areas and then the suburbs. This result may be influenced by parents’ parenting practices, where parents in rural Bukittingi have a higher score on conformity and collectivist parenting than the other two groups.